Uncovering topographically hidden features in 2D MoSe2 with correlated potential and optical nanoprobes - David Moore (Nature Portfolio, 2020)
Abstract Developing characterization strategies to better understand nanoscale features in two-dimensional nanomaterials is of crucial importance, as the properties of these materials are many times driven by nanoscale and microscale chemical and structural modifications within the material. For the case of large area monolayer MoSe2 flakes, kelvin probe force microscopy coupled with tip-enhanced photoluminescence was utilized to evaluate such features including internal grain boundaries, edge effects, bilayer contributions, and effects of oxidation/aging, many of which are invisible to topographical mapping. A reduction in surface potential due to n-type behavior was observed at the edge of the flakes as well as near grain boundaries. Potential phase mapping, which corresponds to the local dielectric constant, depicted local biexciton and trion states in optically-active regions of interest such as grain boundaries. Finally, nanoscale surface potential and photoluminescence mapping was performed at several stages of oxidation, revealing that various oxidative states can be evaluated during the aging process. Importantly, all of the characterization performed in this study was non-destructive and rapid, crucial for quality evaluation of an exciting class of two-dimensional nanomaterials.